СИСТЕМА АВТОМАТИЗОВАНОГО НАЛАШТУВАННЯ ІНТЕЛЕКТУАЛІЗОВАНИХ ЩИТОВИХ ВИМІРЮВАЧІВ ЕЛЕКТРИЧНИХ ПАРАМЕТРІВ ЕНЕРГОГЕНЕРУЮЧИХ ОБ’ЄКТІВ - Кромпляс, Б.А.; Левицький, А.С.; Зайцев, Є. О. (Інститут електродинаміки Національної академії наук України, 2021)
The analysis of functional possibilities of electronic panel meters of electric operational parameters of power generating objects is carried out. The list of additional functions of such meters for the increase of reliability of work of operators of control units of power generating objects is developed. The structure of the automated system of settings of advanced panel meters for different modes of operation of the power generating object is created, the structures and functions of the components of this system are analyzed. Ref. 14, figure.